Strategi Optimalisasi Penggunaan Dana Baznas untuk Pelunasan Piutang Pasien tidak Mampu Bayar pada RSUD Dr. Achmad Mochtar Bukittinggi - Desmon; Yulihasri (CV. ALIM'SPUBLISHING, 2026)
In accordance with Law No. 17 of 2023 on Health, Article 111, paragraph 2 states that both public and private health facilities are prohibited from refusing patients and/or demanding advance payments. The obligation to provide assistance to patients also applies to health workers, as stated in Article 59, paragraph 1 of Law No. 36 of 2014 on Health Workers. hospital administrators or healthcare workers who refuse patients in emergency situations may face criminal charges and fines. In such cases, the hospital must still provide care to patients even if they lack health insurance coverage and are unable to pay the hospital bill, allowing them to be discharged with a Payment Agreement Letter. According to the hospital’s 2024 financial report, there are patient receivables from payment agreements totaling 2 billion rupiah that require a solution to prevent disruption to the hospital’s finances; one potential solution is to utilize zakat funds managed by the UPZ RSAM. Aimed at analyzing the implementation of zakat distribution managed by the UPZ RSAM Bukittinggi and developing strategies for optimizing future zakat distribution, this study was conducted qualitatively using interview and field observation methods, with interview results analyzed using the NVivo application. This strategy for optimizing the use of zakat was developed by focusing on seven research themes: Identification of Policies and Regulations, Optimization Strategies, Organization, Obstacles and Constraints, Program Innovation, and Evaluation.